Gravity Modeling to Understand the Subsurface Geology of the Central Part of West Bandung Regency (Citatah Karst Area, Cipatat-Padalarang) - Suwargana, Hilman; Zakaria, Zufialdi; Muslim, Dicky; Haryanto, Iyan; Wahyudi, Eko Januari; Rohaendi, Nendi (Trends in Sciences, 2023)
Understanding the subsurface system of the central part of West Bandung Regency (including Karst Area), Indonesia, is an important undertaking carried out by geological and geophysical investigations. This research aims to identify geological subsurface features, especially faults,that have an impact on geohazards in the area. To achieve this goal, deep analysis of geology, geomorphology, and geophysical data is conducted. The central part of West Bandung regency is crossed by the Cimandiri Fault, which is located east of the transitional zone between the frontal subduction of Java and the oblique subduction of Sumatra. The preliminary result shows that the active fault has an impact on geohazards (earthquakes and landslides) in the area. Gravity reduction, regional and residual separation, as well as forward modeling with the Pluoff Equation, are all parts of the examination of the gravity data. A second-order polynomial trend surface was subtracted from the entire Bouguer gravity grid to create the residual gravity anomaly map. The amplitudes of the anomalies range from −12 to 8 mGal. The density distribution from the inverse calculation using 4 horizontal line sections (AB, CD, EF, and GH) was set up in the range of −0.3 to +0.3 g/cc. Geological surface markers for the model can be correlated with the information from the Cianjur Sheet geological map. Regional structure is also interpreted in the model to show the main structure of the reverse fault in the study area. HIGHLIGHTS The gravity method using density properties can provide good information about the subsurface karst system Modeling data gravity contributes to an understanding of geological subsurface interpretation Identifying geological subsurface features, especially faults that cause earthquakes and trigger landslides, is part of geohazard mitigation GRAPHICAL ABSTRACT